ANALISIS KINERJA KEUANGAN PADA PT GUDANG GARAM TBK YANG GO PUBLIC DI BURSA EFEK INDONESIA PERIODE 2021-2023 - Johan, Fakhri; Fadlina, Fadlina; Taufiq, Muhammad; Kurniawan, Kurniawan (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study is based on the need to evaluate a company's financial performance as a basis for strategic decision-making by management, investors, and other related parties. PT Gudang Garam Tbk, one of the largest cigarette manufacturers in Indonesia listed on the Indonesia Stock Exchange, experienced fluctuations in performance during the 2021–2023 period, necessitating an in-depth study to assess its financial health. The objective of this study is to analyze the company's financial performance using liquidity, solvency, profitability, and activity ratios and to interpret the findings within the framework of signaling theory. This study employs a quantitative descriptive method with a documentary study approach, where the data analyzed consists of PT Gudang Garam Tbk's audited annual financial statements for the period 2021–2023. The analysis technique used is time series analysis to identify trends in financial performance changes from year to year. The analysis was conducted by calculating the current ratio, quick ratio, debt-to-asset ratio, debt-to-equity ratio, net profit margin, return on assets, return on equity, total asset turnover, and fixed asset turnover. The results of the study show that liquidity ratios are experiencing a downward trend, profitability declined sharply in 2022 and then recovered in 2023, solvency ratios tend to be stable with low financial risk, and activity ratios show fluctuations. Overall, PT Gudang Garam Tbk's financial performance remains below industry standards, but the improvement in 2023 serves as a positive signal according to signaling theory, while the decline in 2022 acts as a negative signal for the market.